On the Triple Meanings of "Jing" in Jingjiao (Chinese Nestorianism) - ZHU, Donghua (Journal of Research for Christianity in China (JRCC), 2025)
The Chinese word “jing 景” embodies three meanings: First, it had a connotation of “light” (guang 光). Modern scholars discuss frequently Christian traits of the Chinese word “jing 景,” because they find that as early as Tang China this term already had taken on a religious connotation when Persian missionaries tried to articulate the divine action in the work of illumination. Second, also noteworthy is the second meaning of “jing 景” invoked by Li Zhizao from the Erya 爾雅, it bears the same meaning of “da 大” (great or universal) as it does in its radical “jing 京.” Third, the brief overview of the Chinese transliterated words of Pahlavi tarsāk suggests Chinese acceptance of the idea of “God-fearers,” and therefore it was no incidental evidence in support of highlighting the usage of “jing 景” as a subtle knowledge of Christian piety. As a broader category for religious practice and belief, “jing” should be holistically understood both from an objective perspective as “shining” or “universal,” and from a subjective perspective as “venerating” or even “fearing (of God).” It is undoubtedly important to expound the meaning of “jing 景” in a dialectical relationship between the piety of believers with respect to the greatness of what is deemed the Sacred.